2016
DOI: 10.1007/s11832-016-0724-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of medial synovial plica excision with and without lateral retinacular release on adolescents with anterior knee pain

Abstract: ObjectivesTo describe the functional outcomes in patients aged ≤18 years with anterior knee pain treated with medial plica excision with or without lateral release.MethodsWe identified 135 patients including 30 bilateral cases (165 knees) with a mean ± SD age of 15.1 ± 2.0 years. Patient and surgical information was recorded and a follow-up athletic questionnaire and an International Knee Documentation Committee (IKDC) Subjective Knee Evaluation form were sent out. Statistical analysis evaluated predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…examined 135 patients at a mean of 4.4 years after arthroscopic plica resection with/without lateral release and found that only 36% of patients were pain-free. 30 Because of the guarded long-term prognosis of surgical treatment, exhaustive conservative management is critical in the treatment of this condition.…”
Section: Operative Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…examined 135 patients at a mean of 4.4 years after arthroscopic plica resection with/without lateral release and found that only 36% of patients were pain-free. 30 Because of the guarded long-term prognosis of surgical treatment, exhaustive conservative management is critical in the treatment of this condition.…”
Section: Operative Managementmentioning
confidence: 99%
“…A common, yet not well understood, cause of anterior knee pain is synovial plica syndrome. 3,4 For the clinician treating pediatric and adolescent patients with knee pain, an understanding of the pertinent anatomy, presentation, physical exam, and imaging is essential so treatment decisions can be made.…”
Section: Introductionmentioning
confidence: 99%